2018
DOI: 10.1111/jop.12759
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐based oral brush cytology in the diagnosis of oral leukoplakia using a modified Bethesda Cytology system

Abstract: Oral liquid-based brush cytology using the Orcellex® brush and ThinPrep® system is a simple and minimally invasive procedure for adequate intraepithelial sampling and can be used as an adjunct for the early detection of oral cancer. The modified Bethesda system established useful means for OLBC assessment that can be utilized in future studies to increase the standardization of oral cytology assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 25 publications
2
80
0
Order By: Relevance
“…In line with previous studies, the Orcellex ® brush has been shown to be useful in harvesting transepithelial cells from oral lesions as there was significant correlation with the corresponding histopathological diagnosis. The sensitivity, specificity, PPV, NPV, and accuracy of OLBC using the modified Bethesda system were satisfactory and consistent with previously published data …”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In line with previous studies, the Orcellex ® brush has been shown to be useful in harvesting transepithelial cells from oral lesions as there was significant correlation with the corresponding histopathological diagnosis. The sensitivity, specificity, PPV, NPV, and accuracy of OLBC using the modified Bethesda system were satisfactory and consistent with previously published data …”
Section: Discussionsupporting
confidence: 83%
“…RA/4/1/9313) and conducted in accordance with the ethical and scientific principles of the Declaration of Helsinki, and the STROBE statement. Cases were selected from an ongoing project evaluating OLBC in diagnosis of OPMD and OSCC . Adult patients aged more than 18 years who were diagnosed with OLK or OSCC were included.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations